Vocational education in the Principality of Liechtenstein - (:unkn) unknown (My University, 1997)
"This brochure has been elaborated by the National Authority of Vocational Education in collaboration with the Leonardo da Vinci Office in Liechtenstein. It gives comprehensive information on vocational education in the Principality of Liechtenstein." (Excerpt, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.2.1 Westeuropa; Berufsbildung; Berufsbildungssystem; Liechtenstein